PROSPEK PENGEMBANGAN POTENSI KESENIAN DAN BUDAYA TRADISIONAL - Andi Sopandi (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
In the context of cultural development in the area of Bekasi today indicate a growing phenomenon of marginalization and getting away from the life of its people. Therefore, the key is to make changes and the identification of potential database Bekasi Traditional Arts and Culture should be done soon, so that will impact on the implementation and regulation conducive to the development of lo-cal arts and culture and tourism. But also very berpengaruhi tripatriet role for the development of cultural arts: the role of government, non-governmental organiza-tions Non-government Organization (NGO) / College / Community arts and cul-ture Industrial World (DU / DI).